(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Recently, parametric criteria of standardized scoring have been used to evaluate the results of surgical treatment, which allows for a comparison of the treatment results reported by various authors in various groups of diseases. This also allows for a comparison of the patients’ condition before and after surgery. For these purposes, scales for parametric scoring of the condition of spinal patients have been developed and are widely used. Using these scales, the condition of patients is assessed both before and after surgery, and the number of points is compared before treatment, immediately after surgery, and in the late period [1]. Extramedullary tumors of the cervical region are a special category of neoplasms of the central nervous system, which is associated predominantly with the benign nature of the process, but is distinguished by a critical location in an anatomical zone of high surgical risk [1, 2]. The location of space-occupying processes in the cervical region, near the neurovascular structures of the brainstem, and sometimes the direct involvement of these structures in the pathological process, has a fatal effect on both the early results of surgical intervention and the late functional consequences. Spinal cord tumors account for approximately 15% of all central nervous system tumors [1]. They are usually benign, and symptoms arise primarily from compression of the spinal cord and nerves [2]. Spinal cord tumors are divided into three groups: extradural, intradural-extramedullary, and intramedullary. Intramedullary spinal cord tumors (ISCTs) are less common, accounting for 2–5% of all spinal cord tumors [3,4]. They originate from the spinal cord tissue itself and lead to invasion and destruction of gray and white matter [5].